HCHs and DDTs in Soils around Guanting Reservoir in Beijing, China: Spatial-Temporal Variation and Countermeasures - Tie-yu Wang; Bing Tan; Yong-long Lu (The Scientific World Journal)
The concentrations of hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs) in the topsoil samples around the Guanting Reservoir in Beijing were measured, and their spatial distribution and environmental risks were analyzed by GIS. The results showed that in 2003, 2007, and 2009, the HCHs concentrations were 0.66, 0.85, and 0.73 ng/g, and the DDTs concentrations were 9.50, 7.80, and 6.46 ng/g in the studied area, respectively. In the topsoil, the HCHs concentrations did not change much while the DDTs concentrations declined steadily. Most of the current residues in soil come from the POPs used in the past years but some new input is also detected in certain regions. The level of HCHs and DDTs residues in the south reservoir is lower than that in the north reservoir. The middle region has the highest HCHs and DDTs concentrations, especially near the Beixinpu town. The high risk regions of pollution of HCHs and DDTs are mainly distributed in the vicinity of Beixinpu town as well. Based on the aforementioned results, a comprehensive countermeasure is proposed entailing decision making, local implementation, scientific support, and public participation with regard to the long-term control and management of POPs around the Guanting Reservoir.